(untitled) - Amir, Pervaiz (Morrilton, Ark., 1989)
The objectives of this book are to give animal scientists the elementary tools to do on-farm livestock analysis and to provide ways for on-farm crop researchers to incorporate the animal component into their studies, thereby making it easier to study complex, mixed farming systems in the developing world.
Keywords: Agriculture,Livestock,Livestock; Research,On-farm,Research,Economic aspects,Research